The Dutch National Research Agenda in Perspective - Molenaar, H.; de Graaf, B.A; Rinnooy Kan, A. (Amsterdam University Press, 2017)
The Dutch National Research Agenda is a set of national priorities that are set by scientists working in conjunction with corporations, civil society organisations, and interested citizens. The agenda consolidates the questions that scientific research will be focused on in the coming year. This book covers the current status of the Dutch National Research Agenda and considers what changes and adjustments may need to be made to the process in order to keep Dutch national research at the top of the pack. Beatrice de Graaf holds one of the chairs of the Dutch National Research Agenda and is chair of History of International Relations and Global Governance at Utrecht University. Alexander Rinnooy Kan holds the other chair of the Dutch National Research Agenda and is university professor of economics and business studies at the University of Amsterdam. Henk Molenaar is the secretary of the Dutch National Science Agenda.